Exploring socioenvironmental influences on adolescent girls eating attitudes in Jakarta : A comparative study - Wangsa, Andrean; Wiradnyani, Luh Ade; Deandra, Fadhila I.; Widyahening, Indah Suci (Indonesian Nutrition Association, 2024)
A balanced diet is vital in adolescence because of the growth spurts occurring in different areas. However, girls in the adolescent phase are at risk of developing unhealthy eating attitudes, leading to severe physical and psychological consequences, including body dissatisfaction, depression, etc. This study was aimed to assessing the socioenvironmental influences on eating attitudes among adolescent girls in DKI Jakarta, Indonesia.